2009
DOI: 10.2131/jts.34.s91
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative work on evaluation of ovarian toxicity 8) Two- or four-week repeated-dose studies and fertility study of Anastrozole in female rats

Abstract: -The main focus of this repeated dose toxicity study was to determine the optimal administration period in terms of toxic effects on ovarian morphological changes. To assess the morphological and functional changes induced by anastrozole in ovaries, the compound was administered to female rats at dose levels of 0, 0.01, 0.1, 1 and 50 mg/kg for 2 or 4 weeks in the repeated dose toxicity study and at levels of 0, 0.01, 0.1, and 5 mg/kg from 2 weeks prior to mating to Day 7 of pregnancy in the female fertility st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
3
8
0
Order By: Relevance
“…This eventually leads to depletion of the ovarian reserve, causing POF [19]. Similarly, busulfan could also cause damage to ovarian function due to its cytotoxic effects [20]. Studies have shown that inflammation and ischemia can be observed in heart, liver, kidney, and spleen tissues of mice after receiving chemotherapy for a week, while changes in each organ could be relieved after 2 weeks without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This eventually leads to depletion of the ovarian reserve, causing POF [19]. Similarly, busulfan could also cause damage to ovarian function due to its cytotoxic effects [20]. Studies have shown that inflammation and ischemia can be observed in heart, liver, kidney, and spleen tissues of mice after receiving chemotherapy for a week, while changes in each organ could be relieved after 2 weeks without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…VPA has been reported to inhibit the conversion from testosterone to estradiol in female rats (Sveberg Roste et al, 2002), primary cultured porcine ovarian follicular cells (Tauboll et al, 2003), and H295R cells (von Krogh et al, 2010). The conversion of testosterone to estradiol is mainly catalyzed by aromatase in the ovarian follicles, and an aromatase inhibitor, anastrozole, induces ovarian toxicity including follicular cyst and abnormal estrous cycle (Shirai et al, 2009). The expression of CYP19, which encodes aromatase, is down-regulated by VPA in H295R cells (von Krogh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While documentation of a decrease in estrogen levels was not possible due to exemestane's interference with the assay, the observed changes in vaginal cytology and the histomorphology of the reproductive tract in treated rats were consistent with aromatase inhibition resulting in decreased estradiol levels (Yano, Ikegami, and Nakao 1996;Baravelle et al 2006;Shirai et al 2009). Furthermore, in rats, treatment with lower doses of exemestane has been shown to decrease ovarian aromatase activity and plasma estradiol levels (Zaccheo et al 1991).…”
Section: Discussionmentioning
confidence: 67%